Epidemiological Features of Hospital Acquired Infection in a Tertiary Military Hospital (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Hospital Acquired Infections (HAIs) are the major concern in developing countries commonly affecting the ill patients in hospital settings. This study was conducted among the surgical patients admitted in the Combined Military Hospital (CMH), Dhaka to see the prevalence of HAI and factors influencing it.Method: The present cross-sectional study was carried out on patients admitted in the Combined Military Hospital (CMH), Dhaka between 01 July to 31 December 2018 to find the epidemiological features of Hospital Acquired Infection (HAI). Patients who acquired infection while admitted in CMH in whom the infection was not present at admission or who were incubating pathogenic microorganisms at the time of admission and manifested signs and symptoms after discharge were the study population. However, psychologically abnormal patients were excluded. A total of 200 patients were selected consecutively. The variables included in the study were demographic characteristics, co-morbidity, immunosuppressive conditions, immunosuppressive therapy.Result: Out 200 patients, 24(12%) developed HAI. Analysis of demographic features revealed that age and sex of the patients did not act as determinants of HAI (0.378 and p = 0.635 respectively). Patients dependent on others for most of their day-to-day activities tend to develop HAI more often than those who did not require assistance in their daily activities (p = 0.005). Patients inserted with an invasive device were more likely to develop HAI (14.9%) than those who were not inserted with such devices (7.6%) (p = 0.121). The patients of chronic respiratory disease and diabetes mellitus frequently develop HAI than the patients with other illnesses (p = 0.040). Colostomy tube was the prime source of HAI (50%) followed by gastrostomy tube (33.3%), urinary catheter (20.6%), orthopedic fixation device (20%) and mechanical ventilation (16.7%) (p< 0.001) with longer the use of invasive devices the higher is the chance of HAI (p = 0.001). No association was observed between immunosuppressive condition of the patients and development of HAI (p = 0.558). Association between immunosuppressive therapy and HAI was not found to be significant (p = 0.495). HAI demonstrated their significant presence in patients with emergency operation compared to that in patients with routine operation (p = 0.047).Conclusion: The study concluded that every one in eight patients admitted in CMH may develop HAI. Patients dependent on others for their daily activities and patients inserted with an invasive device more often develop HAI than those who are independent or without an invasive device. Patients of chronic respiratory disease and diabetes mellitus are more prone to develop HAI. Colostomy and gastrostomy tube also act as the main source of HAI. So does the urinary catheter, orthopedic fixation device and mechanical ventilation with longer the use of invasive devices the higher is the chance of HAI. Emergency operation also tends to be associated with HAI.Ibrahim Card Med J 2019; 9 (1&2): 29-35